Study the Effect of Using Digital Processing on the Original Image Statistically - A.Chachan, Fathala; ., . (International Journal of Engineering and Technology, 2018)
In this paper, we suggested using simple linear regression to determine the extent to which the original image of the changes induced by the use of image processing is affected, and to examine the extent of image similarity by knowing the statistical characteristics of the image before and after treatment,  As well as testing hypotheses related to research and included two main axes:  The first axis deals with the hypothesis of correlation through the use of simple correlation coefficient (Pearson)The second axis highlights the effect relationships by using simple regression analysis for the purpose of testing. The results show that the image after the improvement is closer to the original image through the use of the program Mat lab.